Role of Self-Help Groups in Women’s Empowerment and Sustainable Management of Minor Forest Produce in Rural Chhattisgarh - Shikha Singh; Dr. R. Shridhar; Dr. Monika Sethi Sharma (The Bioscan, 2024)
Minor Forest Produce (MFP) is an important source of income for tribal communities living in forests, and self-help groups (SHGs) are involved in procuring and aggregating MFPs. The sustainable management of natural resources relies heavily on women's contributions. This study aims to focus mainly on the role of SHGs in enhancing the empowerment of women and on assessing the impact of the same on MFP management practices that are concerned with adopting the sustainability approach. To assess how SHG empowered women at the grassroots levels of rural Chhattisgarh, a multidimensional index of empowerment was adopted. 200 women were selected through the stratified sampling method for in-depth surveys and interviews. Data was analyzed using descriptive statistics and regression analysis. The result showed that after joining SHG women are becoming more confident, assertive decision-makers, and better natural resource managers. Self-help groups have the potential to improve environmental and economic results in their communities by focusing on the empowerment of women. This study revealed that empowering women through the formation of SHGs is crucial in determining the sustainable management of minor forest products in rural Chhattisgarh. Therefore, there is a continual requirement for assistance and capacity building of self-help groups for them to continue playing an important role in activities that empower women while also supporting sustainable methods in operating microfinance programs (MFP).